Administration colostrum in preventing mortality and morbidity in preterm infants - Mannan, M. A.; Sihan, M. Nazmus; Afreen, Shazia; Rahman, Tareq; Shahidullah, M.; Moni, Sadeka Choudhury; Shabuj, Kamrul Hassan; Jahan, Ismat (International Journal of Contemporary Pediatrics, 2023)
Background: Oropharyngeal administration of colostrum has found to play a role in preventing the Necrotizing Enterocolitis (NEC), thus reducing mortality and morbidity in preterm infants. We aimed to determine whether early oropharyngeal administration of mother’s own colostrum can reduce the rates of NEC and/or mortality in preterm infants. Methods: We conducted a randomized, placebo controlled, intervention study in Department of Neonatology, Bangabandhu Sheikh Mujib Medical University, Dhaka from 2019 to 2021. Total 92 infants were enrolled, 52 were randomized to oropharyngeal administration of colostrum group and 40 to placebo group. Oropharyngeal administration of colostrum group received maternal colostrum (0.2 ml), after 24 hours of postnatal life and were given every 3 hour for the next 3 days. Serum IgA was measured at 24 hrs and 7th day of postnatal age. Clinical data during hospitalization were collected. SPSS version 21 was used for statistical analysis. Results: Baseline characteristics were comparable and almost similar between the two groups. There was significant reduction in the incidence of NEC stage 2, 16 (30.7%) vs. 26, (65%); p = 0.001). There was significant reduction of age of achieving full enteral feeding (12.1±4.5 vs 19.5±7.5; p = 0.001), disseminated intravascular coagulation (DIC) 12 (23%) vs. 22 (55%); p=0.002, use of mechanical ventilators, 11 (21.1%) vs. 22 (55%); p = 0.001 and number of inotropes (1.2±0.3 vs. 1.61±0.4975; p = 0.002), duration of inotropes (19.7±14.2 vs. 36.5±17.5; p=0.002) in OAC group. However, there was no significant difference in probable sepsis, culture proven sepsis, survival rate and serum IgA level at 1st and 7th day in OAC group, compared to placebo. Conclusions: There was a positive effect in decreasing the incidence of NEC, but no significant effect was observed on survival rate. This intervention facilitates faster achievement of full enteral feeding, reducing the risk of DIC in preterm infants.